Enhancement of Motivation to Learn Hinduism in Students of SMKN 1 Sukawati Gianyar - Putra Sanjaya, Ida Bagus; Budiadnya, Putu (Jayapangus Press, 2024)
Education of religion has contributed to the achievement of national education goals. In this case, there are four components of educational goals whose achievement become the burden of religious education which means they also become the burden of religion teachers, namely having religious spiritual strength, self-control, personality, and noble character. Thus, how great the contribution of religious education and religion teachers in the effort to realize the expected educational goals is. Religious education functions to prepare students to become members of society who understand and practice the values of religious teachings and become experts in religious knowledge as well as increase student learning motivation in studying Hinduism as an effort to contribute to realizing national education goals in Indonesia. Educators can find out the factors that influence student motivation to study Hinduism subjects in school and outside of school because in essence religious people are expected to understand and know the religious teachings adhered to by the humans themselves. The study on the enhancement of motivation among Hindu students in participating in the Hinduism learning process in school was carried out by using observations, interviews, and document studies to obtain qualitative and quantitative data in the form of opinions related to learning problems to increase student’s motivation at SMKN 1 Sukawati Gianyar vocational school. Thus, educators use and improve the curriculum, the competence of Hinduism teachers, student’s motivation, teaching materials, learning models, learning media, facilities and infrastructure, learning environment and school culture towards efforts in implementing the curriculum, applying contextual learning models, increasing the competence of Hinduism teachers, preparing contextual teaching materials, providing learning infrastructure and media, conditioning the learning environment and school culture which is educative as well as praying on full moon and new moon continuously.